1992
DOI: 10.1080/01635589209514170
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and cancer risk

Abstract: The relationship between tea consumption and cancer risk has been analyzed using data from an integrated series of case-control studies conducted in northern Italy between 1983 and 1990. The dataset included 119 histologically confirmed cancers of the oral cavity and pharynx, 294 of the esophagus, 564 of the stomach, 673 of the colon, 406 of the rectum, 258 of the liver, 41 of the gallbladder, 303 of the pancreas, 149 of the larynx, 2,860 of the breast, 567 of the endometrium, 742 of the ovary, 107 of the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
3
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 9 publications
0
67
3
1
Order By: Relevance
“…25 La Vecchia found no association (RR 5 1.0, 95% CI 5 0.7-1.4) in another study in Italy. 26 In this study, ever drinking green tea was positively associated with esophageal cancer risk in both low-and high-risk areas (Dafeng: OR 5 1.2, 95% CI 5 0.9-1.5; Ganyu OR 5 1.9, 95% CI 5 1.4-2.4). But after further adjusting for tea temperature, no significant association was observed either in Dafeng (OR 5 1.0, 95% CI 5 0.7-1.3) or in Ganyu (OR 5 1.3, 95% CI 5 0.9-1.7).…”
Section: Discussionmentioning
confidence: 96%
“…25 La Vecchia found no association (RR 5 1.0, 95% CI 5 0.7-1.4) in another study in Italy. 26 In this study, ever drinking green tea was positively associated with esophageal cancer risk in both low-and high-risk areas (Dafeng: OR 5 1.2, 95% CI 5 0.9-1.5; Ganyu OR 5 1.9, 95% CI 5 1.4-2.4). But after further adjusting for tea temperature, no significant association was observed either in Dafeng (OR 5 1.0, 95% CI 5 0.7-1.3) or in Ganyu (OR 5 1.3, 95% CI 5 0.9-1.7).…”
Section: Discussionmentioning
confidence: 96%
“…26 Furthermore, other data from a pool of Italian case-control studies revealed no association with tea consumption. 10 Data regarding the relationship between tea and cancer are inconsistent. Tea consumption has been inversely associated with all cancers and all-cause mortality; 27 nevertheless, meta-analyses suggested an inverse association of high tea consumption (mainly green tea) only with oral, bladder cancer, leukemia and myeloid malignancies, while less clear data were found for other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…9 On the other side, no association with cancers of the esophagus was found integrating a series of casecontrol studies conducted in Italy. 10 About 90% of adults drink espresso coffee in Italy, while consumption of tea, in particular black tea, is still low.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several epidemiological studies have demonstrated that those who regularly consume tea have a lower incidence of prostate cancer, [82][83][84] while others have shown no association. [85][86][87] The cancer chemopreventive effects of green tea have been attributed to its major polyphenolic constituent, (-)-epigallocatechin-3-gallate (EGCG). 88 Cell-culture experiments on prostate cancer cells by Adhami et al 89 demonstrated that EGCG induces apoptosis, cell-growth inhibition, and cyclin kinase inhibitor WAF-1/p21-mediated cell-cycle dysregulation.…”
Section: Green Teamentioning
confidence: 99%